Navigating relationships with GenAI chatbots: User attitudes, acceptability, and potential - Laura M. Vowels; Rachel R.R. Francois-Walcott; Maëlle Grandjean; Joëlle Darwiche; Matthew J. Vowels (Computers in Human Behavior: Artificial Humans)
Despite the growing adoption of GenAI chatbots in health and well-being contexts, little is known about public attitudes toward their use for relationship support or the factors shaping acceptance and effectiveness. This study aims to address the research gap across three studies. Study 1 involved five focus groups with 30 young people to gauge general attitudes toward GenAI chatbots in relationship contexts. Study 2 evaluated user experiences during a single relationship intervention session with 20 participants. Study 3 quantitatively measured changes in attitudes toward GenAI chatbots and online interventions among 260 participants, assessed before, immediately after, and two weeks following their interaction with a GenAI chatbot or a writing task. Three main themes emerged in Studies 1 and 2: Accessible First-Line Treatment, Artificial Advice for Human Connection, and Internet Archive. Additionally, Study 1 revealed themes of Privacy vs. Openness and Are We in a Black Mirror Episode?, while Study 2 uncovered themes of Exceeding Expectations and Supporting Neurodivergence. The Study 3 results indicated that GenAI chatbot interactions led to reduced effort expectancy and short-term effects in increased acceptance and decreased objections to GenAI chatbots, though these effects were not sustained at a two-week follow-up. Both intervention types improved general attitudes toward online interventions, suggesting that exposure can enhance the uptake of digital health tools. This research underscores the evolving role of GenAI chatbots in augmenting therapeutic practices, highlighting their potential for personalized, accessible, and effective relationship interventions in the digital age.